2021
DOI: 10.1186/s12893-021-01232-0
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Imaging (HSI) as a new diagnostic tool in free flap monitoring for soft tissue reconstruction: a proof of concept study

Abstract: Objectives Free flap surgery is an essential procedure in soft tissue reconstruction. Complications due to vascular compromise often require revision surgery or flap removal. We present hyperspectral imaging (HSI) as a new tool in flap monitoring to improve sensitivity compared to established monitoring tools. Methods We performed a prospective observational cohort study including 22 patients. Flap perfusion was assessed by standard clinical param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 43 publications
(51 reference statements)
2
37
1
Order By: Relevance
“…While we could not reproduce the promising results of Goetze et al in our study and are unable to recommend the device for perforator detection with the described cooling protocol, it has been demonstrated to be of significant value following surgical anastomosis for perfusion monitoring and to detect underperfused areas within the flap in other studies [48,49]. Some authors postulate it to be even more effective than the gold standard for flap monitoring, clinical assessment and handheld Doppler [50,51]. Similar aspects are valid for LD imaging.…”
Section: Discussioncontrasting
confidence: 54%
“…While we could not reproduce the promising results of Goetze et al in our study and are unable to recommend the device for perforator detection with the described cooling protocol, it has been demonstrated to be of significant value following surgical anastomosis for perfusion monitoring and to detect underperfused areas within the flap in other studies [48,49]. Some authors postulate it to be even more effective than the gold standard for flap monitoring, clinical assessment and handheld Doppler [50,51]. Similar aspects are valid for LD imaging.…”
Section: Discussioncontrasting
confidence: 54%
“…As previously described, HSI allows to assess tissue viability using four different parameters, namely tissue oxygenation (StO 2 %), the near-infrared perfusion index (NIR%), the tissue hemoglobin index (THI%), and the tissue water index (TWI%). A study by Kohler et al reported that StO 2 % and NIR% were more suitable for skin flap perfusion monitoring when compared to THI% and TWI%, as StO 2 % and NIR% provided more information regarding the microcirculation in the superficial layers of the skin [ 20 ]. The results of the current study are in congruence with the ones of Kohler et al since StO 2 % is the most suitable parameter for the assessment of skin viability, with an accuracy of 93%.…”
Section: Discussionmentioning
confidence: 99%
“…The first use of HSI to intraoperatively determine tissue perfusion was reported in 2001 [ 17 ]. Although tissue perfusion assessment is currently the main indication to perform HSI [ 18 , 19 , 20 , 21 , 22 , 23 ], it is also used for wound analysis and for the differentiation between healthy skin and skin cancer [ 24 , 25 ]. A hyperspectral camera system provides the possibility of measuring hemoglobin levels, with oxyhemoglobin (O 2 Hb) and de-oxyhemoglobin (HHb) as its derivatives, and to analyze tissue oxygenation patterns (StO 2 %) and near-infrared (NIR%), tissue hemoglobin (THI%), and tissue water (TWI%) perfusion indices [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, HSI has found an application in plastic surgery. In fact, in two clinical trials, the authors have used this technology to assess the viability of free and pedunculated flaps intraoperatively and in the postoperative phase [50,51]. In both studies, it was concluded that the perfusion variations displayed with HSI correlated well with the clinical behavior (failure or healing) of the grafts.…”
Section: Perfusion Assessment In Reconstructive Surgerymentioning
confidence: 99%